Pathogen Evasion of Chemokine Response Through Suppression of CXCL10 - Antonia, Alejandro L.; Gibbs, Kyle D.; Trahair, Esme D.; Pittman, Kelly J.; Martin, Amelia T.; Schott, Benjamin H.; Smith, Jeffrey S.; Rajagopal, Sudarshan; Thompson, J. Will; Reinhardt, Richard Lee; Ko, Dennis C. (Frontiers in Cellular and Infection Microbiology, 2019)
Clearance of intracellular pathogens, such as Leishmania (L.) major, depends on an immune response with well-regulated cytokine signaling. Here we describe a pathogen-mediated mechanism of evading CXCL10, a chemokine with diverse antimicrobial functions, including T cell recruitment. Infection with L. major in a human monocyte cell line induced robust CXCL10 transcription without increasing extracellular CXCL10 protein concentrations. We found that this transcriptionally independent suppression of CXCL10 is mediated by the virulence factor and protease, glycoprotein-63 (gp63). Specifically, GP63 cleaves CXCL10 after amino acid A81 at the base of a C-terminal alpha-helix. Cytokine cleavage by GP63 demonstrated specificity, as GP63 cleaved CXCL10 and its homologues, which all bind the CXCR3 receptor, but not distantly related chemokines, such as CXCL8 and CCL22. Further characterization demonstrated that CXCL10 cleavage activity by GP63 was produced by both extracellular promastigotes and intracellular amastigotes. Crucially, CXCL10 cleavage impaired T cell chemotaxis in vitro, indicating that cleaved CXCL10 cannot signal through CXCR3. Ultimately, we propose CXCL10 suppression is a convergent mechanism of immune evasion, as Salmonella enterica and Chlamydia trachomatis also suppress CXCL10. This commonality suggests that counteracting CXCL10 suppression may provide a generalizable therapeutic strategy against intracellular pathogens.